Antenatal steroids are associated with a reduction in the incidence of cerebral white matter lesions in very low birthweight infants. Issue 2 (1st March 2002) - Agarwal, R; Chiswick, M L; Rimmer, S; Taylor, G M; McNally, R J Q; Alston, R D; D'Souza, S W
Abstract : Aims: To investigate whether antenatal steroids reduce the incidence of cerebral white matter lesions in very low birthweight infants. Methods: A total of 224 newborn infants of < 31 weeks gestational age and weighing < 1500 g was studied between January 1998 and June 2000. Obstetric and neonatal information was obtained from the case notes. The study population was subdivided into two groups according to antenatal steroid exposure. A complete course of treatment consisted of two doses of 12 mg each of betamethasone given at an interval of 12–24 hours. Infants in group 1 were born to mothers who had not received betamethasone, or were delivered within 24 hours of receiving the first dose of steroid. Infants in group 2 were born to mothers who had received one or more complete courses of betamethasone and were delivered > 24 hours after receiving the first dose of steroid. Results: The two groups contained statistically similar proportions of boys and girls, and the infants had similar birth weights and survival rates. Those in group 2, compared with those in group 1, had a lower gestational age (p = 0.02) and a lower incidence of white matter lesions on cranial ultrasound scans (p = 0.03). Stepwise logistic regression analysis showed that gestational age (p = 0.0002) and a complete course of antenatal steroids (p = 0.02) had independent effects on cerebral white matter lesions. Conclusions: These observations suggest that a complete course of antenatal steroids may have a protective effect against cerebral white matter lesions in very low birthweight infants.